EFL Young Learners’ Problems Encountered in the Learning of English Speaking: Teachers’ Perspectives - Nikmah, Nur Syafira; Anwar, Choiril (Register Journal, 2021)
Teaching speaking to Indonesian EFL young learners is still problematic. It happens not only because English is not used in daily activities but also the government’s regulation to some extent does not support that. This qualitative study aims to describe the problems faced by EFL students in the learning of English speaking with teachers’ perspectives. The samples of this research were three teachers from three different elementary schools in Jepara, Central Java, Indonesia. The data were collected by using questionnaire, interview, and classroom observation. The data were then analyzed by 1) memoing or transcribing the interview data, reading them to make notes and finding the most important information that might be useful for the study, 2) describing the data to find complete explanation of context, setting, and interactions of participants, 3) classifying data—to break down the obtained result and put it into categories, and 4) interpreting the data to find the meanings of the data by connecting the findings with previous studies, personal experience, and expert advice to find the best result. The result showed that EFL students’ problems in the learning of English speaking came from some factors. They are 1) Native language, 2) Age, 3) Exposure, and 4) Motivation, and 5) Learners’ Autonomy. Keywords: speaking, Indonesian EFL students, young learners